Pengaruh Lama Waktu Biofermentasi Chromolaena odorata dengan Sumber Karbon Gula Lontar Cair terhadap Kandungan Energi - Leki, Sindi Rambu; Dami Dato, Twen O; Mullik, Marthen Luther; Benu, Imanuel (Animal Agricultura, 2024)
This study aims to determine the duration of Chromolaena odorata biofermentation with liquid palm sugar carbon source on energy content. The method used in this research is experimental method to test 4 treatments of fermentation time on Chromolaena odorata. The research design used was a completely randomized design (CRD) with 4 treatments and 4 replicates so that there were 16 experimental units. The treatments were: LB-0 = without biofermentation, LB-7 = 7 days biofermentation duration, LB-14 = 14 days biofermentation duration, LB-21 = 21 days biofermentation duration. Variables observed were carbohydrate content, BETN, gross energy, metabolic energy and TDN. Data were analyzed by variance analysis at 5% alpha level, differences between treatments were tested by Duncan's multiple tests. The results showed that the duration of Chromolaena odorata biofermentation with liquid palm sugar carbon source had a very significant effect (P=0.001) on BETN content (37.94-43.89%), GE content (4,282-4,429 kcal/kg BK), and EM content (3,067-3,443 kcal/kg BK), while the carbohydrate content (60.02-62.69%) and TDN content (61.60-63.80%) had no significant effect (P=0.07 and 0.27). It was concluded that the length of time of Chromolaena odorata biofermentation with liquid palm sugar carbon source increased energy content, with the best length of time for carbohydrate, BETN, and TDN for 7 days; GE for 14 days, while EM for 21 days.